Изотопная дефектоскопия материалов и изделий - Горбунов В. И. Владимир Иванович; Кузнецов В. Б.; Кулешов В. К. Валерий Константинович; Янкелевич Ю. Б. Юзеф Бенционович; Янкелевич Я. Б. (1965, 1965)
Заглавие с титульного листа